Determinant of Profitability of State of Enterprise in Indonesia: Merger Case - ., Sudaryono; Hakim, Dedi Budiman; Manurung, Adler Haymans; Asikin, Zenal (Journal of Ecohumanism, 2025)
The research is aimed to analyze determinants of profitability performance (ROA, ROE, and PER) of Indonesia’s state-owned enterprises, using mergers and acquisitions a moderating factor. The research employs panel data analysis to estimate the effect of Revenue, Current Ratio, Debt to Equity Ratio, Exchange Rate, Oil Price, and COVID-19 on Profitability for the period of observation of 2010 – 2021. The result shows that Revenue performs significant impact on ROA, ROE, and PER. Moreover, the Current Ratio also performs significant impact on ROA, ROE, and PER. Furthermore, Debt to Equity Ratio performs significant impact on ROA and PER. In terms of the macroeconomic factor, the exchange rate significantly affects ROA and ROE. This researh also reveals that investors use mergers and acquisitions news to seek for profits (through stock purchase) to earn potential higher capital gain. On the other hand, the empirical result indicates a significant difference of the company’s performance (ROA and ROE) before and after the period of mergers and acquisitions. However, the difference seems to be insignificant for the Price to Earnings Ratio (PER). The empirical result implies the urgency to optimize the long run impact of mergers and acquisitions of Indonesia’s state-owned enterprises.